Verrucous hemangioma expresses primitive markers1. (4th February 2013) - Laing, Emma L.; Brasch, Helen D.; Steel, Ryan; Jia, Jun; Itinteang, Tinte; Tan, Swee T.; Day, Darren J.
<x xml:space="preserve">Abstract</x> Background Verrucous hemangioma (VH) presents clinically as a vascular malformation but has similar histopathologic features to infantile hemangioma. This study characterized the cell population within VH. Material and methods Paraffin‐embedded sections from two male patients with VH were processed for immunohistochemistry. The expression of SMA, CD34, glucose transporter‐1 (Glut‐1), D2‐40, brachyury, angiotensin converting enzyme (ACE), Oct‐4, hemoglobin ζ chain (HBZ), Wilms tumor protein (WT‐1) and CD45 was examined. Results The lymphatic marker, D2‐40, was not expressed in VH, whereas Glut‐1 was widely expressed in infantile hemangioma, it was only focally expressed by the endothelium of VH. The endothelium of VH expressed the primitive markers, Oct‐4, brachyury and ACE. The primitive marker, WT‐1, was expressed predominantly on the pericyte layer of both VH and infantile hemangioma. However, HBZ was only expressed in infantile hemangioma. CD45, a mature hematopoetic marker, was expressed by cells within the interstitium, away from the endothelium of VH and infantile hemangioma. Discussion The expression of the primitive markers, Oct‐4, brachyury and ACE on the endothelium, and WT‐1 predominantly on the pericyte layer of VH shows a primitive microvascular phenotype similar to infantile hemangioma. However, the absence of the embryonic marker, HBZ, expressed only in first trimester placenta and in proliferating infantile hemangioma, suggests a different cellular origin. HBZ could be used to distinguish between the two conditions.